Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

Potentials of a friction-induced recycling process to improve resource and energy efficiency in manufacturing technology - Borgert, Thomas; Milaege, Dennis; Schweizer, Swetlana; Homberg, Werner; Schaper, Mirko; Tröster, Thomas (International Journal of Material Forming)
Abstract Efforts to enhance sustainability in all areas of life are increasing worldwide. In the field of manufacturing technology, a wide variety of approaches are being used to improve both resource and energy efficiency. Efficiency as well as sustainability can be improved by creating a circular economy or through energy-efficient recycling processes. As part of the interdisciplinary research group "Light—Efficient—Mobile" investigations on the energy-efficient friction-induced recycling process have been carried out at the department of Forming and Machining Technology at Paderborn University. E.g. using the friction-induced recycling process, different formless solid aluminum materials can be direct recycled into semi-finished products in an energy-efficient manner. The results of investigations with regard to the influence of the geometrical shape and filling rate of the aluminum particles to be recycled as well as the rotational speed of the continuously rotating wheel are explained in this paper. In addition to the recycling of aluminum chips, aluminum particles like powders from the field of additive manufacturing are processed. Based on these results, the future potentials of solid-state recycling processes and their contribution to the circular economy are discussed. The main focus here is on future interdisciplinary research projects to achieve circularity in the manufacturing of user-individual semi-finished products as well as the possibility to selectively adjust the product properties with the continuous recycling process.
Keywords: General Materials Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

Tax Complexity, Tax Department Structure, and Tax Risk - Giese, Henning; Koch, Reinald; Sureth-Sloane, Caren

Dietary flavonoids among children and adolescents in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study: intake, food sources and trends from 1985 until 2016 - Rienks, Johanna; Penczynski, Katharina J.; Schmitting, Sarah; Buyken, Anette; Nöthlings, Ute (British Journal of Nutrition)
Abstract Flavonoids are suggested to reduce disease risk. Since dietary habits are acquired during early life, describing age and time trends of flavonoid intake and major food sources are important for monitoring and disease prevention in later life. We aimed to describe total flavonoid intake and food sources and to investigate age and time trends of flavonoid intake in 3–18-year-olds, from the Dortmund Nutritional and Anthropometric Longitudinally Designed study from 1985 to 2016. Intake was assessed annually using 3-d weighed food records (WFR). Flavonoid values were assigned using the United States Department of Agriculture database. Foods contributing to intake were determined. Age and time trends in total flavonoid and isoflavone density were analysed by sex with PROC MIXED. In total, 1312 children completed 10 758 WFR. Across all ages, daily mean total flavonoid density was lower in boys compared with girls (134 v . 146 mg/4184 kJ) and no difference in median isoflavone density (0·04 mg/4184 kJ per d) was found. The top five foods contributing to total flavonoid intake were apple with peel (15·0/17·1 %), strawberries (5·9/6·1 %), chocolate spread (3·9/3·5 %), orange juice (3·5/3·4 %) and pasta (3·5/3·4 %) for boys and girls, respectively. Overall, in boys, total flavonoid density decreased over the course of age and time. In girls, there was no association with age or time. In both sexes, isoflavone density followed a U-shaped age trend with no change over time. From a public health perspective, the overall observed downwards trend of flavonoid intake in boys deserves attention. Future initiatives should be tailored at maintaining a high flavonoid density as children age, specifically among boys.

Business Intelligence & Analytics Cost Accounting: A Survey on the Perceptions of Stakeholders - Grytz, Raphael; Krohn-Grimberghe, Artus (Proceedings of the 51st Hawaii International Conference on System Sciences)
As data driven decision-making using business intelligence and analytics (BI&A) becomes standard in companies, the importance of mitigating the accompanying growth in costs increases. Research shows that increasing transparency to the granularity of individual BI&A artefacts such as reports or analytic applications is a necessary means, but in practice the introduction of said systems is cumbersome and adoption is slow. We address the status quo of BI&A cost accounting for three types of stakeholders: users, developers and managers. The results show in which areas of application a strong need for action exists and we identify major challenges for further research are ahead. Our findings indicate for example that managers at the same time regard cost accounting for BI&A with a higher potential benefit while they also believe they have already established a higher degree of implementation in their enterprises compared to the other stakeholder types. We conclude that BI&A professionals have to consider these different perceptions to run a successful department and gain traction for BI&A cost accounting.

A Summary of Survey Methodology Best Practices for Security and Privacy Researchers - Redmiles, Elissa M.; Acar, Yasemin; Fahl, Sascha; Mazurek, Michelle L.

Geschlechteridentitäten von Jugendlichen im Kontext von Social Media. Jahrestagung der Fachstelle Gender NRW (FUMA) am 26. Juni 2014 in der Volkshochschule Düsseldorf - Richter, Susanne (GENDER – Zeitschrift für Geschlecht, Kultur und Gesellschaft)
Zusammenfassung Auf der Tagung der Fachstelle Gender NRW (FUMA) „Geschlechteridentitäten von Jugendlichen im Kontext von Social Media“, die am 26.06.2014 in Düsseldorf stattfand, stand der Umgang mit neuen Medien im Mittelpunkt. Diskutiert wurden die Praktiken von Jugendlichen in sozialen Netzwerken und die Herausforderungen, die sich hieraus für Mitarbeitende der Kinder- und Jugendhilfe ergeben. Dabei wurde auch der Frage nach Auswirkungen auf Geschlecht und Geschlechtsidentitäten nachgegangen. Schlüsselwörter Internet, Neue Medien, Web 2.0, Pädagogik, Jugendarbeit, Geschlechtsidentität Summary Adolescent Gender Identities in the Context of Social Media. Annual conference of the specialist department Gender NRW (FUMA), Düsseldorf, 26 June 2014. The conference “Adolescent Gender Identities in the Context of Social Media” was held in Düsseldorf on 26 June 2014 and was hosted by the specialist department Gender NRW (FU-MA). It focused on the use of new media. Participants discussed adolescents’ practices in social networks and the resulting challenges for youth work professionals. The influence on gender and gender identity was also investigated. Keywords internet, new media, web 2.0, science of education, youth services, gender identity

The corporate marketing department - Between value and vanish - Ritter, T; Eggert, A; Münkhoff, E; Ulaga, W (ISBM 2014 Academic Conference)